Pengembangan Lembar Kerja Peserta Didik (LKPD) Materi Sistem Koloid Berbasis Pendekatan Saintifik - Ermelinda Hoar Halek; Theresia Wariani; Anselmus Boy Baunsele; Erly Grizca Boelan (Journal on Education, 2024)
The Student Activity Sheet (LKPD) is a learning media that can be used to support the learning process. Students either individually or in groups can build their own knowledge with a variety of learning resources. The purpose of this study is to determine the validity of the LKPD based on a Scientific Approach to colloidal system material. This research is based on the results of observations related to teaching and learning activities during the Covid-19 pandemic. This type of research is quantitative descriptive research. The result of this study is LKPD based on a scientific approach to colloidal system material that is compiled to have a high level of validity, where the percentage value of validity for the material is 100% with very valid criteria, while the percentage value of validity for language is 92% with very valid criteria. Thes, LKPD based on a Scientific approach to Colloidal System material is suitable for use in the teaching and learning process